PENGARUH KUALITAS LAYANAN MOBILE BANKING DAN TINGKAT KEPERCAYAAN TERHADAP KEPUASAN NASABAH BANK NTB SYARIAH CABANG SUMBAWA - Dery Sofya , Nora; Heriwibowo, Dedy; Rodianto (Jurnal TAMBORA, 2020)
This study aims to determine the effect partially and simultaneouslyquality of mobile banking services and level of confidence in customer satisfactionBank NTB Syariah, Sumbawa Branch. This research is descriptive researchquantitative. The type of data used is primary data obtained from the resultsdistributing questionnaires to customers of Bank NTB Syariah, Sumbawa Branch.The sample in the study was 100 respondents who were user customersBank NTB Syariah Sumbawa Branch mobile banking service. Data analysis methodused is multiple linear regression which includes partial test, simultaneous test, and testthe coefficient of determination. The results showed that partially and simultaneouslyservice quality and customer trust level have a positive and significant effectto customer satisfaction of users of mobile banking services. Apart from that, abilityindependent variable in explaining the dependent variable based on the value of Adjusted R Square76.9% and the remaining 23.1% is influenced by other variables that are notdiscussed in this study.